Fibre segment interferometry for dynamic strain measurements - Kissinger, Thomas; Correia, Ricardo N.; Charrett, Thomas O. H.; James, Stephen W.; Tatam, Ralph P. (Institute of Electrical and Electronics Engineers (IEEE), 2016)
Using a novel range-resolved interferometric signal processing technique based on the sinusoidal optical frequency modulation of a cost-effective laser diode, a fibre sensing approach termed fibre segment interferometry (FSI) is described. In FSI, a chain of long-gauge length fibre optic strain sensors are separated by identical in-fibre partial reflectors. Targeted at dynamic strain analysis and ultrasound detection for structural health monitoring, this approach allows integrated strain measurements along fibre segments, removing the sensing gaps and sensitivity to inhomogeneities found with localized fibre sensors. In this paper, the multiplexing of six fibre segments, each of length 12.5 cm, is demonstrated. The sensor array can be interrogated at 98 kHz data rate, achieving dynamic strain noise levels 0:14 n Hz 0:5. The reflector fabrication is discussed, an analysis of linearity and noise performance is carried out and results from an exemplar experiment to determine the speed-of-sound of a stainless steel rod are shown.
Keywords: Optical fibre sensors; Fiber gratings; Optical interferometry; Strain measurement; Condition monitoring